A Case Report on Dapagliflozin-Associated Euglycemic Diabetic Ketoacidosis Triggered by Acute Viral Gastroenteritis: Case Report (Journal of Pharma Insights and Research, 2026)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors represent a cornerstone in the modern management of type 2 diabetes mellitus, offering substantial benefits beyond glycemic control, including significant reduction in cardiovascular mortality and slowing the progression of chronic kidney disease. However, the emergence of euglycemic diabetic ketoacidosis (EDKA) as a rare but life-threatening complication poses a diagnostic challenge for clinicians. Unlike the traditional presentation of diabetic ketoacidosis, EDKA is characterized by severe metabolic acidosis and ketonemia in the presence of near-normal or only mildly elevated blood glucose levels, often leading to delayed recognition and intervention. A 52-year-old male with a twelve-year history of type 2 diabetes mellitus presented to the emergency department with symptoms of profound dehydration, nausea, and abdominal pain following a brief period of acute viral gastroenteritis and reduced oral intake. Despite a serum glucose concentration of 186 mg/dL, laboratory findings confirmed a high-anion-gap metabolic acidosis (pH 7.2, bicarbonate 12 mmol/L) and significant ketosis (β-hydroxybutyrate 7.1 mmol/L). The patient had been consistently using 10 mg of dapagliflozin daily. Clinical recovery was achieved through the immediate cessation of the SGLT2 inhibitor, aggressive fluid resuscitation, and a specialized protocol involving concurrent insulin and dextrose infusions to resolve the acid-base imbalance while maintaining normoglycemia. This case shows the necessity of "sick-day" education for patients on SGLT2 inhibitors and the need for mandatory ketone assessment in any diabetic patient presenting with systemic illness, regardless of blood glucose levels